Twelfth night - "Shakespeare" (Sweet cherry publishing: China, 2013)
Twelfth Night by William Shakespeare is a delightful comic love story. The play begins with a shipwreck, during which Viola, a young aristocratic-born woman, is separated from her identical twin brother, Sebastian, and is swept onto the shores of the Kingdom of Illyria. Thus begins this entertaining tale of mistaken identities and thwarted love. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource. The easy-to-read narration and comic-style illustrations are sure to captivate children s interest and develop their reading skills
Keywords: Adaptation Juvenile Literature